Hypoperfusion Intensity Ratio Is Correlated With Patient Eligibility for Thrombectomy. Issue 4 (April 2019) - Guenego, Adrien; Marcellus, David G.; Martin, Blake W.; Christensen, Soren; Albers, Gregory W.; Lansberg, Maarten G.; Marks, Michael P.; Wintermark, Max; Heit, Jeremy J.
Abstract : Background and Purpose—: Hypoperfusion intensity ratio (HIR) is associated with collateral status in acute ischemic stroke patients with anterior circulation large vessel occlusion. We assessed whether HIR was correlated to patient eligibility for mechanical thrombectomy (MT). Methods—: We performed a retrospective cohort study of consecutive acute ischemic stroke patients with a proximal middle cerebral artery or internal carotid artery occlusion who underwent MT triage with computed tomography or magnetic resonance perfusion imaging. Clinical data, ischemic core (mL), HIR (defined as time-to-maximum [TMax] >10 seconds/TMax >6 seconds), mismatch volume between core and penumbra, and MT details were assessed. Primary outcome was favorable HIR collateral score (HIR <0.4) between patients who underwent MT (MT+) and those who did not (MT−) according to American Heart Association guidelines both in the <6 hours and 6 to 24 hours windows. Secondary outcomes were favorable HIR score in MT− subgroups (National Institutes of Health Stroke Scale <6 versus core >70 mL) and core-penumbra mismatch volumes. Patients who did not meet guidelines were not included. Results—: We included 197 patients (145 MT+ and 52 MT−). MT+ patients had a significantly lower median HIR compared with MT− patients (0.4 [interquartile range, 0.2–0.5] versus 0.6 [interquartile range, 0.5–0.8]; P <0.001) and a higher mismatch volume (96 versus 27 mL, P <0.001). Among MT− patients, 43 had a core >70 mL, and 9 had a National Institutes of Health Stroke Scale <6. MT− patients with National Institutes of Health Stroke Scale <6 had a lower HIR than MT− patients with core >70 mL (0.2 [interquartile range, 0.2–0.3] versus 0.7 [interquartile range, 0.6–0.8], P <0.001) but their HIR was not significantly different that MT+ patients. Conclusions—: Patients who meet American Heart Association guidelines for thrombectomy are more likely to have favorable collaterals (low HIR). HIR may be used as a marker of eligibility for MT triage. Abstract : Supplemental Digital Content is available in the text.